2020
DOI: 10.1002/cam4.2965
|View full text |Cite
|
Sign up to set email alerts
|

ASCT2 overexpression is associated with poor survival of OSCC patients and ASCT2 knockdown inhibited growth of glutamine‐addicted OSCC cells

Abstract: BackgroundAlanine‐serine‐cysteine transporter 2 (ASCT2), a major glutamine transporter, is essential for cell growth and tumor development in a variety of cancers. However, the clinicopathological significance and pathological role of ASCT2 in OSCC (oral squamous cell carcinoma) lesions remain unclear.MethodsSections from 89 OSCC patients and 10 paracancerous tissue controls were stained by immunohistochemistry (IHC) to detect the expression of ASCT2, glutaminase, and Ki‐67. Survival analysis was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…ASCT2 is overexpressed in squamous cell carcinoma, adenocarcinoma, and neuroendocrine lung cancers [ 41 ]. In addition, overexpression of ASCT2 in oral squamous cell carcinoma is positively correlated with poor outcomes [ 42 ]. ASCT2 serves as an obligatory exchanger that imports a sodium-coupled amino acid substrate into cells and exports another sodium-coupled amino acid substrate with 1:1 stoichiometry [ 43 , 44 ].…”
Section: Asct2 (Slc1a5)mentioning
confidence: 99%
See 1 more Smart Citation
“…ASCT2 is overexpressed in squamous cell carcinoma, adenocarcinoma, and neuroendocrine lung cancers [ 41 ]. In addition, overexpression of ASCT2 in oral squamous cell carcinoma is positively correlated with poor outcomes [ 42 ]. ASCT2 serves as an obligatory exchanger that imports a sodium-coupled amino acid substrate into cells and exports another sodium-coupled amino acid substrate with 1:1 stoichiometry [ 43 , 44 ].…”
Section: Asct2 (Slc1a5)mentioning
confidence: 99%
“…System Xc(-) takes up cystine in exchange for glutamate for GSH synthesis, whereas ASCT2 imports glutamine in a cooperative manner [ 28 , 48 ] ( Figure 2 ). Thus, targeted knockdown of ASCT2 inhibits GSH synthesis and induces ferroptosis mediated by the accumulation of intracellular redox stress [ 42 ].…”
Section: Asct2 (Slc1a5)mentioning
confidence: 99%
“…The blockade of glutamine metabolism represents an interesting approach to reduce cancer cell growth, by depriving the cells of the fuel which they need to proliferate [64]. It could be particularly useful to combat aggressive cancers characterized by a large expression of ASCT2, such as advanced laryngeal and oral squamous cell carcinoma [65][66][67]. Such an inhibition of glutamine uptake via down-regulation of ASCT2 in cancer cells has been previously observed with established anticancer drugs, like topotecan used to treat gastric cancer [68].…”
Section: Anticancer Activity Of Lobetyolinmentioning
confidence: 99%
“…ASCT2, an alanine, serine, cysteine-preferring trans-porter, mediated the uptake of glutamine, a conditionally essential amino acid in rapidly proliferating tumor cells. 24 There has been an increased focus on glutamine transport and metabolism as a putative therapeutic target owing to its high expression in many cancers. Previous studies have shown that glutaminolysis is a key component of the metabolic reprogramming of myofibroblasts and fibrosis progression in mice with liver fibrosis, which provides clues for understanding the role of ASCT2 in HSC activation and reversion.…”
Section: Discussionmentioning
confidence: 99%